Molecular Imaging and Non-molecular Imaging of Atherosclerotic Plaque Thrombosis - Bingchen Guo; Zhaoyue Li; Peiyang Tu; Hao Tang; Yingfeng Tu (Frontiers in Cardiovascular Medicine, 2021)
Thrombosis in the context of atherosclerosis typically results in life-threatening consequences, including acute coronary events and ischemic stroke. As such, early detection and treatment of thrombosis in atherosclerosis patients is essential. Clinical diagnosis of thrombosis in these patients is typically based upon a combination of imaging approaches. However, conventional imaging modalities primarily focus on assessing the anatomical structure and physiological function, severely constraining their ability to detect early thrombus formation or the processes underlying such pathology. Recently, however, novel molecular and non-molecular imaging strategies have been developed to assess thrombus composition and activity at the molecular and cellular levels more accurately. These approaches have been successfully used to markedly reduce rates of atherothrombotic events in patients suffering from acute coronary syndrome (ACS) by facilitating simultaneous diagnosis and personalized treatment of thrombosis. Moreover, these modalities allow monitoring of plaque condition for preventing plaque rupture and associated adverse cardiovascular events in such patients. Sustained developments in molecular and non-molecular imaging technologies have enabled the increasingly specific and sensitive diagnosis of atherothrombosis in animal studies and clinical settings, making these technologies invaluable to patients' health in the future. In the present review, we discuss current progress regarding the non-molecular and molecular imaging of thrombosis in different animal studies and atherosclerotic patients.